The Impact of Pipe Material on the Diversity of Microbial Communities in Drinking Water Distribution Systems - Lee, Debbie; Calendo, Gennaro; Kopec, Kristin; Henry, Rebekah; Coutts, Scott; McCarthy, David; Murphy, Heather M. (Frontiers in Microbiology, 2021)
As many cities around the world face the prospect of replacing aging drinking water distribution systems (DWDS), water utilities must make careful decisions on new pipe material (e.g. cement-lined or PVC) for these systems. These decisions are informed by cost, physical integrity, and impact on microbiological and physicochemical water quality. Indeed, pipe material can impact the development of biofilm in DWDS that can harbor pathogens and impact drinking water quality. Annular reactors (ARs) with cast iron and cement coupons fed with chloraminated water from a municipal DWDS were used to investigate the impact of pipe material on biofilm development and composition over 16 months. The ARs were plumbed as closely as possible to the water main in the basement of an academic building to simulate distribution system conditions. Biofilm communities on coupons were characterized using 16S rRNA sequencing. In the cast iron reactors, -proteobacteria, Actinobacteria, and -proteobacteria were similarly relatively abundant (24.1%, 22.5%, and 22.4%, respectively) while in the cement reactors, -proteobacteria and Actinobacteria were more relatively abundant (36.3% and 35.2%, respectively) compared to -proteobacteria (12.8%). Mean alpha diversity (estimated with Shannon H and Faith’s Phylogenetic Difference indices) was greater in cast iron reactors (Shannon: 5.00 ± 0.41; Faith’s PD: 15.40 ± 2.88) than in cement reactors (Shannon: 4.16 ± 0.78; Faith’s PD: 13.00 ± 2.01). PCoA of Bray-Curtis dissimilarities indicated that communities in cast iron ARs, cement ARs, bulk distribution system water, and distribution system pipe biofilm were distinct. The mean relative abundance of Mycobacterium spp. was greater in the cement reactors (34.8 ± 18.6%) than in the cast iron reactors (21.7 ± 11.9%). In contrast, the mean relative abundance of Legionella spp. trended higher in biofilm from cast iron reactors (0.5 ± 0.7%) than biofilm in cement reactors (0.01 ± 0.01%). These results suggest that pipe material is associated with differences in the diversity, bacterial composition, and opportunistic pathogen prevalence in biofilm of DWDS.